2023
DOI: 10.3389/fphar.2023.1133961
|View full text |Cite
|
Sign up to set email alerts
|

Functional selectivity of EM-2 analogs at the mu-opioid receptor

Abstract: The mu opioid receptor agonists are the most efficacious pain controlling agents but their use is accompanied by severe side effects. More recent developments indicate that some ligands can differentially activate receptor downstream pathways, possibly allowing for dissociation of analgesia mediated through the G protein from the opioid-related side effects mediated by β-arrestin pathway. In an effort to identify such biased ligands, here we present a series of thirteen endomorphin-2 (EM-2) analogs with modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“… 602 Biased agonists with reduced β-arrestin 2 recruitment, like 2S-LP2 and EM-2, are being developed to alleviate these effects. 603 , 604 However, there are dissenting opinions that β-arrestin 2 as a scaffolding protein is unlikely to be an ideal pharmacological target. Evidences have shown that severe side effects are not observed in mice with ablation of β-arrestin 2 functions, 605 , 606 implying that unknown mechanisms independent of β-arrestin 2 may contribute to chronic opioid tolerance.…”
Section: Intervention Methods For Pain Reliefmentioning
confidence: 99%
“… 602 Biased agonists with reduced β-arrestin 2 recruitment, like 2S-LP2 and EM-2, are being developed to alleviate these effects. 603 , 604 However, there are dissenting opinions that β-arrestin 2 as a scaffolding protein is unlikely to be an ideal pharmacological target. Evidences have shown that severe side effects are not observed in mice with ablation of β-arrestin 2 functions, 605 , 606 implying that unknown mechanisms independent of β-arrestin 2 may contribute to chronic opioid tolerance.…”
Section: Intervention Methods For Pain Reliefmentioning
confidence: 99%